Soil quality and eggplant productivity in response to different mulching strategies under conservation tillage in organic greenhouse production - Amami, Roua; Ibrahimi, Khaled; Tarchoun, Neji; Saadaoui, Wassim; Boughattas, Nour El Houda; Ghazouani, Hiba; Sher, Farooq; Jones, Davey L.; Milham, Paul (Frontiers in Agronomy, 2025)
IntroductionMulching is a key practice in sustainable agriculture that improves soil quality, conserves resources, and enhances crop performance. However, comparative assessments of different mulch types under organic greenhouse conditions remain limited, particularly in semi-arid environments.MethodsA field experiment was conducted in an unheated greenhouse using a randomized complete block design with three replications. Five treatments were tested: black polyethylene mulch (BM), white polyethylene mulch (WM), straw mulch (SM), compost mulch (CM), and a bare soil control (CK). The study evaluated the impact of these treatments on soil physicochemical properties, microbial communities, and eggplant (Solanum melongena L.) growth and yield under organic farming conditions.ResultsWhite mulch significantly increased soil pH, while CK resulted in the highest soil electrical conductivity. BM maintained the highest soil temperature and water content across all dates. CM significantly enhanced soil organic matter (+0.32 g kg⁻¹), available phosphorus (+41 mg kg⁻¹), potassium (+302 mg kg⁻¹), and total nitrogen (+5.33 mg kg⁻¹) compared to CK. SM promoted the greatest microbial abundance, including bacteria, mesophilic and thermophilic fungi. The Soil Quality Index (SQI) ranged from 0.34 to 0.58, with BM recording the highest value and CK the lowest. BM also led to significant improvements in plant growth metrics and yield, with a 29.5 t ha⁻¹ increase over the other treatments.DiscussionPlastic mulch, particularly black polyethylene, proved to be the most effective in enhancing soil conditions, microbial activity, and eggplant productivity in the short term. These results highlight its potential as a cost-effective strategy for improving crop performance and soil resilience in semi-arid organic greenhouse systems. Nonetheless, further long-term studies across diverse environments and soil types are necessary to confirm the broader applicability of these findings